Examining Social Acceptability of Solar Innovations in Smart Cities - Khurshid, Muhammad M.; Shehzad, Hafiz M. Faisal; Rashid, Ammar; Adeel, Umar (Civil Engineering Journal, 2025)
Objective: The global challenge of climate change and the need for energy conservation have prompted a reevaluation of energy sources and policies worldwide. This study aims to investigate the societal acceptability of solar photovoltaic (PV) systems among citizens of smart cities, an aspect crucial yet underexplored in the context of renewable energy technologies. Methods/Analysis: A comprehensive survey was conducted involving 560 respondents to assess public perceptions, attitudes, and behaviors toward solar PV systems. The study also examined the moderating effects of area (urban/rural), gender, trust, and duration of use (experience) on societal acceptability. Findings: The results show that both independent and moderating variables significantly influence the social acceptability of solar innovations in smart cities. Key factors identified include the user-friendly design of solar systems, effective awareness campaigns highlighting their benefits, and compatibility with existing technologies. These elements are crucial in fostering positive attitudes and intentions towards the adoption of solar energy. Novelty/Improvement:This research provides valuable insights for policymakers, energy planners, and researchers, emphasizing the importance of considering demographic and experiential factors in policy-making. The findings suggest that societal acceptance of solar PV systems can be enhanced by targeting area-specific needs, leveraging trust, and promoting the benefits of prolonged usage experience. Doi: 10.28991/CEJ-2025-011-02-016 Full Text: PDF